Acute change of lung function to short-term exposure to ambient air pollutants with and without physical activity: A real-world crossover study. (1st January 2023) - Guo, Qian; Zhao, Yuchen; Zhao, Jiahao; Bian, Mengyao; Qian, Liqianxin; Xue, Tao; Zhang, Junfeng (Jim); Duan, Xiaoli
Abstract: Physical activity (PA) would increase the inhalation rate and thereby inhaled dose of air pollutants. However, it's still uncertain whether the effects of air pollutants on lung function are attenuated by PA, especially in the high-polluted areas. We aimed to disentangle the interaction between air pollution and PA on lung function among healthy adults. In this study, a real-world crossover study was conducted among 74 healthy adults. Each participant underwent both rest and 15-min intermittent moderate PA exposure scenarios (consisting of 15min stationary bike riding alternating with 15min of rest), which lasted for 2 h. On the same day, the participants among active and inactive group were exposed to the same air pollution. We have monitored the fine particulate matter (PM2.5 ), particulate matter less than 10 μm (PM10 ), particulate matter less than 1 μm (PM1 ), black carbon (BC), nitrogen dioxide (NO2 ), and ozone (O3 ) continuously during 2-h exposure. Lung function were measured at five times points for each visit (before, immediately, 3 h, 5 h, and 24 h after the 2-h exposure scenario). Mixed-effects models were applied to explore the effects of air pollution, PA, and their interaction on lung function. The participants had a mean (standard deviation (SD)) age of 19.9 (0.9) years. The average concentration [mean ± SD] of PM2.5, PM10, PM1, BC, NO2, and O3 were 59.4 ± 45.1 μg/m 3, 122.8 ± 109.0 μg/m 3, 38.8 ± 29.2 μg/m 3, 1.94 ± 1.17 μg/m 3, 59.5 ± 26.6 μg/m 3, and 74.0 ± 30.3 μg/m 3, respectively. Overall, greater increasement in lung function were observed among active group compared with inactive group at all timepoints. In fully adjusted models, we observed the benefits of PA and detrimental effects of air pollutants on lung function. Our results suggested that PA, compared to rest, alleviated the detrimental effects of air pollutants on lung function. We also stressed the importance of timing of measurements for capturing association. In conclusion, our observations suggested that PA might alleviate the associations between various pollutant exposures and lung function, which would drive further research towards potential pathway. Graphical abstract: Image 1 Highlights: Interaction of PA and air pollution were explored by crossover design. PA benefits to lung function, while air pollution had detrimental effects. PA alleviated the associations between air pollution and lung function. It's critical to capture the time point on the negative associations of air pollution.